A method to value nature-related webcam viewing: the value of virtual use with application to brown bear webcam viewing. Issue 4 (2nd October 2018) - Loomis, John; Richardson, Leslie; Huber, Chris; Skibins, Jeffrey; Sharp, Ryan
ABSTRACT: There are an estimated 16, 000 nature related remote web cameras that provide users around the world with an opportunity to view wildlife. Because there is no monetary price to view the webcams, we utilise variations in the viewers' opportunity cost of time to estimate consumer surplus. We apply this model to a large sample ( n = 2649) of the more than 10 million viewers of Alaska's Katmai National Park and Preserve brown bear webcams. The resulting consumer surplus is around 11 per hour of viewing. When applied to the 2.42 million viewer hours, this yields a benefit of 27 million annually. Since there are limits on the number of visitors as well as high costs of visiting this remote site, the aggregate webcam viewing value is more than twice the aggregate on-site viewing value. With minimal survey data required to apply this model, we believe it has broad applicability to other nature-related webcams around the world.